Aplikasi Web Prototipe untuk Peminjaman dan Pengembalian Buku di STMIK Pesat Nabire - Ester Ayuk Pusvita; Fernando Ewak; Arief Rahman Hakim (Jurnal Publikasi Teknik Informatika, 2025)
The development of information technology has a significant impact on the information management system, including in the higher education environment. STMIK Pesat Nabire as one of the educational institutions needs an efficient, modern, and easily accessible library system. This research aims to design and build a web-based library application that can facilitate book data management, borrowing, returning, and searching for information online. The development of this application uses the prototype method, which allows the development process to be carried out iteratively and flexibly through continuous collaboration between developers and users. The main features in the app include book data management, members, loan and return transactions, and late notifications. The test results showed that the built system could run well and meet the needs of users in the STMIK Pesat Nabire environment. With this application, it is hoped that library services will be more effective and efficient, and able to increase the reading interest of the academic community.